Non-rigid connector: The wand to allay the stresses on abutment - Saurav Banerjee; Arlingstone Khongshei; Tapas Gupta; Ardhendu Banerjee (Wolters Kluwer Medknow Publications, 2011)
The use of rigid connectors in 5-unit fixed dental prosthesis with a pier abutment can result in failure of weaker retainer in the long run as the pier abutment acts as a fulcrum. Non-rigid connector placed on the distal aspect of pier seems to reduce potentially excess stress concentration on the pier abutment.